Assessment of foot type and comparison of anthropometric foot dimension between foot types of Indian population: A pilot study - Rajib Jana; Ayan Maity; Sugata Das Kumar; Madhusudan Pal (Al Ameen Journal of Medical Sciences)
Background: Human foot morphology is essential for enhancing the fit and comfort of foot-related products in fields like orthopedics, orthotic design, and sports sciences. Objectives: This study aims to collect foot anthropometric dimensions, categorize foot types, and compare these dimensions among the Indian population. Materials and Methods: A total of 162 male volunteers (average age: 28.20 ± 12.95 years, height: 165.62 ± 6.27 cm, weight: 63.33 ± 6.70 kg) participated. Measurements were taken using a 3D foot scanner, and data analysis was performed using SPSS version 26. Results: The study found that 53.08% of participants had the Egyptian foot type, followed by 46.91% with the square foot type. Square foot measurements were generally higher than Egyptian feet, except for foot arch height. Significant differences (p<0.05) were observed in waist circumference, toe circumference, and heel center width between the two-foot types. The Egyptian foot type showed lower values in all dimensions compared to the square foot type. However, all foot parameters for the square foot type were higher than the pooled data, except for foot arch height. Conclusion: The most prevalent foot shapes among Indian males are the square and Egyptian types. The study recommends designing adult-specific shoes based on these foot types.